Performing water in Nigeria: Ecocritical (re)negotiations of hydro-aesthetics in Ojo Bakare’s “Ekun Omi” - Princewill Chukwuma Abakporo; Ooreofe-kristi T. Faniyi; Ofega Eru; Precious Kufre Udoh; Mary Bosede Aiyetoro (Resital: Jurnal Seni Pertunjukan, 2025)
Against mounting concerns over Nigeria’s increasingly vulnerable aqua-terrestrial environment, this study examines the potential of the performing arts, particularly music and theatre, as tools of ecological engagement. It re-evaluates the agency and significance of water as a natural element, a life-sustaining force, and a geographical resource within the context of persistent aquatic degradation. To achieve this, the study analyzes the aesthetics, musical, and dramatic permutations in the production of Ojo Bakare’s Ekun Omi. Drawing on ecocriticism, conceptual metaphor, and the case study approach of the qualitative research method, the study analyses how the performance presents water not only a life support of nature, but also as an active agent that can (and has started to) withstand years of exploitation and extraction in Nigeria. With precise emphasis on lyrics, rhythm, melody, vocal texture, instrumentation, movement, dialogues and characterization in the play, this study investigates how water—both as a metaphor in the play and as a real-world element—has started to renegotiate its essence in ways that now pose a long-term threat to Nigeria's environmental futures. The fusion of theatre and music in "Ekun Omi" offers a multi-layered environmental discourse that aims to dismantle anthropogenic legacies while promoting locally based frameworks for environmental stewardship. Through the explorations of the embodied, musical, and dramaturgical conduits in which water is performed, this study advances the call for improved eco-musicological and eco-theatrical presence in ecological discourse. Finally, the study validates the synergy of music and theatre as powerful tools to push environmental concerns from the domains of knowledge to the domain of feeling, even as it positions "Ekun Omi" as a pungent intervention in Nigeria's politics of ecological repair. The researchers believe that this shift should be the starting point for any significant environmental stewardship initiative in Nigeria.